DAMPAK PENYALAHGUNAAN NARKOBA TERHADAP PRESTASI AKADEMIK SISWA - Ahmad Iqbal; Syamsu A Kamaruddin (STKIP Subang, 2026)
This study aims to analyze the impact of drug abuse on the academic performance of students through a comprehensive literature review. Using a qualitative descriptive approach and library research techniques, the study synthesizes findings from books, scholarly articles, and institutional reports that examine how drug abuse disrupts cognitive, psychological, and social functioning. The review indicates that drug abuse significantly impairs academic performance due to decreased concentration, memory disturbances, reduced motivation, and emotional instability. These cognitive and psychological disruptions are often accompanied by behavioral problems such as absenteeism, low participation, difficulty completing assignments, and a higher likelihood of dropping out. Social consequences—including damaged relationships with peers, family, and teachers—further weaken students’ academic engagement. Evidence from national data and international studies also shows that drug abuse can lead to health complications, increased risk-taking behavior, and long-term dependency that profoundly affects students’ learning capacity and educational trajectory. In educational settings, the presence of drug abuse disrupts the learning environment, reduces productivity, and undermines school quality. These findings underscore the urgent need for preventive and intervention efforts within schools, involving collaboration among educators, families, and communities. Strengthening awareness, early detection, and targeted mentoring programs is essential to mitigate the detrimental effects of drug abuse and support students in achieving optimal academic outcomes. Keywords: drug abuse, academic performance, cognitive impairment, learning motivation, qualitative research